(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
Walking through the streets of Concepción, in silence, suddenly the word would emerge and, thereafter, something absurd, unexpected amidst the fog: voices embraced by the rhythm of the rain, music, expectant speech. Jaime Giordano believes in the voice that hides, whose mode of communication is intimate confession, reserved prayer, the word as a ritual of closure.